Study on the Nationalization in the Development of Chinese Popular Music - Chen, Yanan; Jamnongsarn, Surasak; Rodsakan, Tepika (Journal of Roi Kaensarn Academi, 2023)
In the course of decades of development of Chinese popular music, many times of national expansion have been formed, fully showing the unique cultural personality of Chinese pop music.This study focuses on three important upsurges of the nationalization of Chinese pop music.Looking at the existing academic theoretical achievements, it has not paid enough attention to the nationalization of Chinese pop music, and has not formed a clear theoretical description of the reasons, characteristics, performance, and social influence of nationalization.Therefore, this study strives to fill the research gaps in these aspects with practical actions. Through the analysis of historical documents and audio-visual videos, it can fully demonstrate the course of the nationalization of Chinese popular music, and promote it to form a more distinctive and better development in the future. Promoting Chinese contemporary pop music culture can demonstrate the cultural charm of the oriental power in an independent way that combines Chinese and Western styles.